Short Review on Polycystic Ovarian Syndrome - Farooq, Rabia (Journal of Medicine, 2017)
Polycystic ovarian syndrome (PCOS) is a metabolic disease and a common endocrine system disorder among women of reproductive age. Infrequent or prolonged menstrual periods, excess hair growth, acne, and obesity can occur in women with PCOS. Early diagnosis and treatment along with weight loss may reduce the risk of long-term complications. Now a days PCOS is also the cause of infertility. India is PCOS capital of the world. PCOS management is necessary to reduce its long time complications. J MEDICINE Jan 2018; 19 (1) : 49-53